Location choices under strategic interactions - Alcácer, Juan; Dezső, Cristian; Zhao, Minyuan (Strategic Management Journal, 2015)
We explore a fundamental aspect of firms' location choices largely overlooked in the literature: strategic interaction. We formalize the notion that strategic interaction renders collocation less appealing by fostering competition, which erodes firms' profits. Strategic interaction also impacts location choices across time. Specifically, because firms learn by doing in markets, location choices are shaped by two novel effects: entrenchment benefits from entering early in a market and improving capabilities relative to rivals, and opportunity costs from postponing entry to other markets where rivals enter and learn. When learning is local, firms collocate more: rivals are preempted from improving relative capabilities in higher‐value markets. However, when learning is global, firms collocate less: they can transfer capabilities from lower‐value to higher‐value markets, blocking rivals from achieving entrenchment benefits . Copyright © 2013 John Wiley & Sons, Ltd.